HUBUNGAN KEBERSIHAN WAJAH TERHADAP KEJADIAN AKNE VULGARIS PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS MALAHAYATI ANGKATAN 2018 - Amalia Shofifah Anggraeni; Rakhmie Rafie; Anggunan; M. Syafei Hamzah (Medula, 2022)
Acne vulgaris (AV) is a chronic inflammatory disease of pilosebaceous follicles that can heal itself with multifactorial causes and has several clinical features in the form of acne, comedones, papules, pustules, nodes, and cysts. Factors causing the appearance of acne vulgaris are usually influenced by bacterial infection, excessive use of cosmetics, hormones and lack of hygiene. Performing facial hygiene can reduce bacteria or microorganisms from the skin surface by reducing sebum and dirt without removing the lipid barrier of the skin so as to reduce AV symptoms